Effects of Pin1 Loss in HdhQ111 Knock-in Mice - Agostoni, Elena; Michelazzi, Silvia; Maurutto, Marta; Carnemolla, Alisia; Ciani, Yari; Vatta, Paolo; Roncaglia, Paola; Zucchelli, Silvia; Leanza, Giampiero; Mantovani, Fiamma; Gustincich, Stefano; Santoro, Claudio; et al. (Frontiers in Cellular Neuroscience, 2016)
Huntington’s disease (HD) is a fatal, dominantly inherited, neurodegenerative disorder due to a pathological expansion of the CAG repeat in the coding region of the HTT gene. In the quest for understanding the molecular basis of neurodegeneration, we have previously demonstrated that the prolyl isomerase Pin1 plays a crucial role in mediating p53-dependent apoptosis triggered by mutant huntingtin (mHtt) in vitro. To assess the effects of the lack of Pin1 in vivo, we have bred Pin1 knock-out mice with HdhQ111 knock-in mice, a genetically precise model of HD. We show that Pin1 genetic ablation modifies a portion of HdhQ111 phenotypes in a time-dependent fashion. As an early event, Pin1 activity reduces the DNA damage response. In midlife mice, by taking advantage of next-generation sequencing technology, we show that Pin1 activity modulates a portion of the alterations triggered by mHtt, extending the role of Pin1 to two additional HdhQ111 phenotypes: the unbalance in the “synthesis/concentration of hormones”, as well as the alteration of “Wnt/β-catenin signaling”. In aging animals, Pin1 significantly increases the number of mHtt-positive nuclear inclusions while it reduces gliosis. In summary, this work provides further support for a role of Pin1 in HD pathogenesis.